Cava Smoothie As An Adjuvant in Iron Supplementation Can Increase Hemoglobin Levels and Erythrocyte Indices in Anemic Adolescent Girls - Aryani, Vina Dinata Kamila; Muthmainah, Muthmainah; Nuhriawangsa, Adi Magna Patriadi (Media Gizi Indonesia, 2023)
Uncontrolled anemia leads to a decline in hemoglobin levels and erythrocyte blood indices, posing various health risks. To address this, a study aimed to assess the effectiveness of cava smoothies and iron supplementation in boosting hemoglobin levels and erythrocyte indices among anemic adolescent girls. The study involved 87 adolescent girls with moderate anemia, divided into three groups. The control group (C) received weekly iron tablets (60 mg), while two intervention groups (I1 and I2) were given the same iron tablets along with cava smoothies in increasing doses over 28 days. The results revealed significant improvements in hemoglobin levels. Group C showed an increase of 0.27 g/dL, while I1 and I2 demonstrated remarkable gains of 1.46 g/dL and 2.54 g/dL, respectively. Furthermore, erythrocyte indices (MCV, MCH, MCHC) exhibited positive changes. Group C saw increases of 0.35 fl, 0.34 pg, and 0.27 g/dL, I1 showed improvements of 0.69 fl, 0.61 pg, and 0.64 g/dL, and I2 experienced substantial enhancements of 1.97 fl, 1.61 pg, and 1.60 g/dL. In conclusion, the study confirmed that cava smoothies and iron supplementation effectively raise hemoglobin levels and improve erythrocyte indices in anemic adolescent girls, highlighting the potential benefits of this intervention for combating anemia.